The Role of Technology in ELL Classes in Turkish Republic of Northern Cyprus - Barzani, Sami Hussein Hakeem; Aslam, Muhammad Zammad; Aslam, Talha (International Journal of Language Education, 2021)
In the contemporary English language classroom, technology keeps an important role to support language learning. The present research focuses only on the tools, i.e., Smart Boards, tablets/laptops, and LMS (online learning management system), which English language teachers utilize in their class at the level of English Preparatory School, BS and Master in the Turkish Republic of Northern Cyprus (TRNC). Moreover, the present qualitative and observational research examines the role of technology, which is utilized at the English Preparatory School in Cyprus International University to teach English to the learners who learn English as a Second Language. For the present research, the researchers collect the data through 2 interviews of the teachers who teach at Cyprus International University (CIU) and from an in-depth literature review. Through the findings of the present research, the researchers observe that: a) all the teachers in TRNC utilize technology, i.e., Smart Boards, tablets and LMS during the teaching of English language and English subjects, i.e., Multimedia (only for PowerPoint presentations); b) in TRNC, the technology helps the English Language Learners (ELLs) to enhance their language skills and make them independent language learners; c) in TRNC, teachers, and students who utilize technology in language learning process face technical challenges due to lack of knowledge or less familiarity with the technology. Hence, the present research would explore the pros and cons of technology and intends the knowledge of a teacher who would take an interest in teaching language through technology.